New inequalities for a class of differentiable functions - Dahmani, Zoubir (International Journal of Nonlinear Analysis and Applications, 2011)
In this paper, we use the Riemann-Liouville fractional integrals to establish some new integral inequalities related to Chebyshev’s functional in the case of two differentiable functions.
Keywords: Chebyshev’s functional, Differentiable function, Integral inequalities, Riemann-Liouville fractional integral.